A comprehensive analysis of candidate genes in familial pancreatic cancer families reveals a high frequency of potentially pathogenic germline variants - Earl, Julie; Galindo Pumariño, Cristina; Encinas, Jessica; Barreto, Emma; Castillo, María Encarnación; Pachon, Vanessa; Ferreiro, Reyes; Rodríguez Garrote, Mercedes; González Martínez, Silvia; Ramon y Cajal, Teresa; Robles Diaz, Luis; Chirivella Gonzalez, Isabel; et al. (My University, 2020)
Background: The 5-year survival rate of patients with pancreatic ductal adenocarcinoma (PDAC) is around 5% due to the fact that the majority of patients present with advanced disease that is treatment resistant. Familial pancreatic cancer (FPC) is a rare disorder that is defined as a family with at least two affected first degree relatives, with an esti mated incidence of 4% 10%. The genetic basis is unknown in the majority of families although around 10% 13% of families carry germline mutations in known genes associated with hereditary cancer and pancreatitis syndromes. Methods: Panel sequencing was performed of 35 genes associated with hereditary cancer in 43 PDAC cases from families with an apparent hereditary pancreatic cancer syndrome. Findings: Pathogenic variants were identified in 19% (5/26) of PDAC cases from pure FPC families in the genes MLH1, CDKN2A, POLQ and FANCM. Low frequency potentially pathogenic VUS were also identified in 35% (9/26) of PDAC cases from FPC families in the genes FANCC, MLH1, PMS2, CFTR, APC and MUTYH. Furthermore, an important proportion of PDAC cases harboured more than one pathogenic, likely pathogenic or potentially pathogenic VUS, highlighting the multigene phenotype of FPC. Interpretation: The genetic basis of familial or hereditary pancreatic cancer can be explained in 21% of families by previously described hereditary cancer genes. Low frequency variants in other DNA repair genes are also present in 35% of families which may contribute to the risk of pancreatic cancer development.